Pemanfaatan Media Sosial Tiktok sebagai Pemasaran Hasil Pertanian Desa Gajah Kecamatan Simpang Empat Kabupaten Tanah Karo - Eka Putri Saptari Wulan; Eunike Pasaribu; Cindi Kristiani Gea; Ika Lovika Purba (Lembaga Pengembangan Kinerja Dosen, 2024)
The TikTok application is now loved by many people (Haryanto 2020). The TikTok application is now loved by many people. to increase promotion and public understanding of activities in Gajah Village, Kec. Simpang Empat District. Karo land. Carrying out community service (PkM), the team of community service students from HKBP Nommensen University, Medan, will provide exposure and training on the use of Tiktok social media as a means of promoting activities in Gajah Village, Kec. Simpang Empat District. Karo land. In Community Service, Gajah Village is categorized as one of the villages located under the foot of Mount Sinabung. The Gajah Village Office is led by Mr. Erguna Karo-karo as Village Head at the Gajah Village Office. The address of Gajah Village is Gajah Village, District. Simpang Empat, Regency. Tanah Karo in North Sumatra Province. It is hoped that there will be an increase in knowledge and management of TikTok social media so that people's welfare and economy will increase due to increasing demand for agricultural products. TikTok social media is a marketing effort using electronic/internet devices with various marketing tactics and digital media where we can communicate with potential consumers online.